2018
DOI: 10.1016/j.ultsonch.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Control Al/Mg intermetallic compound formation during ultrasonic-assisted soldering Mg to Al

Abstract: To prevent the formation of Al/Mg intermetallic compounds (IMCs) of AlMg and AlMg, dissimilar Al/Mg were ultrasonic-assisted soldered using Sn-based filler metals. A new IMC of MgSn formed in the soldered joints during this process and it was prone to crack at large thickness. The thickness of MgSn was reduced to 22 μm at 285 °C when using Sn-3Cu as the filler metal. Cracks were still observed inside the blocky MgSn. The thickness of MgSn was significantly reduced when using Sn-9Zn as the filler metal. A 17 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…After ultrasonic degassing, the molten Pb 90 Sn 10 is well treated and can well be used. In the newly done experiments, the flowability of ultrasonically treated filler alloy is moving inside Si intervals at a faster speed; the texture filling rate is higher than 99.9% [13] . Meanwhile, the flowing speed of Pb-Sn when with ultrasonic excitation is more even swift, we have observed that all the pastes can be well soldered within 10 seconds.…”
Section: Test Results and Discussionmentioning
confidence: 98%
“…After ultrasonic degassing, the molten Pb 90 Sn 10 is well treated and can well be used. In the newly done experiments, the flowability of ultrasonically treated filler alloy is moving inside Si intervals at a faster speed; the texture filling rate is higher than 99.9% [13] . Meanwhile, the flowing speed of Pb-Sn when with ultrasonic excitation is more even swift, we have observed that all the pastes can be well soldered within 10 seconds.…”
Section: Test Results and Discussionmentioning
confidence: 98%
“…Formation of the intermetallic layers between the interfaces of the initial plates will be unavoidable if laminated composites or welded different metal alloys have been fabricated at high temperatures or apply a preheating process. 2225 These intermetallic compounds and their structures determine the performance of the joint. 26 In this area, Yazdani et al 27 studied the fabrication of Al-matrix nanocomposites reinforced by mono-dispersed TiAl3 intermetallic three-step process of cold-roll bonding, heat-treatment, and accumulative roll bonding.…”
Section: Introductionmentioning
confidence: 99%
“…In general, this difficulty can be solved by two methods, adopting solid-state bonding process or alloying the weld seam. Friction stir welding (FSW) [ 3 , 4 , 5 , 6 , 7 , 8 ], resistance spot welding (RSW) [ 9 ], contact-reaction brazing [ 10 , 11 , 12 ], ultrasonic spot welding [ 13 , 14 , 15 ] and explosive welding [ 16 , 17 , 18 ] were employed for joining Mg–Al dissimilar metals, and the formation of IMCs was restrained by reducing the reaction temperature and reaction time of the liquid metal. However, decreasing the heat input could not completely eliminate the brittle IMCs in the joint.…”
Section: Introductionmentioning
confidence: 99%